GÜÇLENMEYİ GÜÇ, GÜÇSÜZLÜK, BASKI VE GÜÇ İLİŞKİLERİ TEMELİNDE ANLAMAK. - CANKURTARAN, Özlem; AKOĞLU, Gizem; SAKARYA, Hakan (Journal of Society & Social Work / Toplum ve Sosyal Hizmet, 2020)
Beside the traditional social work knowledge and value base, the empowerment approach involves understanding and analyzing oppression, and experiencing the empowerment process by focusing on power and oppression. In the relevant literature, it is seen that power is discussed with its conceptual dimensions, there is no information and discussion on how power relations can be analyzed by focusing on power relations. This article, which is structured on the basis of the concepts of power, powerlessness and oppression, discusses the issue of empowerment that started with Jane Addams in social work discipline and profession is emphasized along with historical view on power and powerlessness. The aim of this study is to discuss the concept of power and historicalness of power, and to understand how individuals are weakened with the use of oppression and oppression tools, and understand the empowerment process which are the analysis steps of power relations, and enabling change in power relations with the development of critical consciousness by understanding, exploring, reframing the power relations. As a result, emphasizing the importance of empowerment in social work for achieving beloved, equitable and fair community, it is argued that there is a need for a paradigm change based on empowerment in the social work knowledge and practice.